2010
DOI: 10.1093/ndt/gfq617
|View full text |Cite
|
Sign up to set email alerts
|

The podocyte as a direct target of immunosuppressive agents

Abstract: Podocytes play a key role in maintaining the blood-urine barrier for high-molecular-weight proteins. They are considered to be terminally differentiated, and podocyte loss cannot be compensated by regenerative proliferation. Various diseases leading to podocyte damage and loss result in proteinuria and cause nephrotic syndrome. Therefore, direct therapeutical strategies to protect podocytes in disease situations are a logical concept to prevent disease or to delay disease progression. Acquired podocytopathies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
90
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 72 publications
2
90
1
Order By: Relevance
“…Nephrotic syndrome (NS) is a complex and non-specific disease characterized by severe proteinuria (> 3.5 g/day), hypoproteinemia, generalized edema, hyperlipidemia and, occasionally, hypertension [1]. Generally, NS base might reflect multiple immunological disorders [2], a critical filtration barrier breakage or could follow diabetes mellitus [3,4], obesity [5], sarcoidosis [6] as well as different malignancies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotic syndrome (NS) is a complex and non-specific disease characterized by severe proteinuria (> 3.5 g/day), hypoproteinemia, generalized edema, hyperlipidemia and, occasionally, hypertension [1]. Generally, NS base might reflect multiple immunological disorders [2], a critical filtration barrier breakage or could follow diabetes mellitus [3,4], obesity [5], sarcoidosis [6] as well as different malignancies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In a previous study, we implicated ER stress in the development of the rodent model of minimalchange disease (MCD). 9 There are a number of studies suggesting that podocyte damage underlies the development of MCD; 10,11 however, the pathophysiological mechanisms of proteinuria have not been fully elucidated. In the rodent puromycin aminonucleoside (PAN) model of MCD, we showed upregulation of GRP78, a molecular chaperone stimulated by ER stress, in podocytes on days 4 and 5 at a heavy proteinuric state; we also showed that this GRP78 upregulation was associated with a change in the cellular localization of nephrin from the plasma membrane to the cytoplasm.…”
mentioning
confidence: 99%
“…6,7 The podocyte clearly plays a critical role in maintaining the glomerular filtration barrier and structural integrity; thus, podocyte injury and loss contribute to proteinuria and progressive sclerosis. 8 For instance, one report indicates that the podocyte expresses receptors for interleukin-4 and interleukin-13, which, if activated by these cytokines, might disrupt glomerular permeability resulting in proteinuria. 9 Podocyte injury can occur in several immunologic and nonimmunologic diseases of the kidney.…”
mentioning
confidence: 99%
“…Notably, immunosuppressive agents such as corticosteroids and calcineurin inhibitors are known to protect the podocyte against injury and loss by stabilizing its actin cytoskeleton, cell maturation, and survival: an action that underscores their anti-proteinuric effect in idiopathic nephrotic syndrome. 8 In fact, the use of calcineurin inhibitors as the initial therapy for children with steroid-resistant nephrotic syndrome (SRNS) is the current evidence-based recommendation in the treatment guideline for glomerulonephritis. 10 Idiopathic MCN (SSNS) and FSGS (SRNS) require early differentiation in order to ensure prompt therapeutic intervention and better outcome.…”
mentioning
confidence: 99%